ANALISIS TINDAK TUTUR EKSPRESIF DALAM FILM MOANA 2 - Naufa Rayluna; Silawarti Harahap; Mauliza Armi (IKIP Siliwangi, 2025)
Language functions not only as a means of conveying messages but also as a primary medium for expressing emotions, attitudes, and the cultural values of a society. Film, as a product of popular culture, intensively employs language to construct characters and develop the storyline, including through the use of expressive speech acts. This study aims to examine the forms and functions of expressive speech acts in the film Moana 2 using a pragmatic approach. The research applies a descriptive qualitative method with observation and note-taking techniques to analyze dialogues between characters that contain expressive speech acts. The findings indicate that Moana 2 presents various types of expressive speech acts, such as praise, expressions of happiness, astonishment, anger, sadness, and gratitude, which reflect the emotional dynamics of the characters. These speech acts play an important role in strengthening characterization, building relationships among characters, and conveying moral values such as affection, responsibility, courage, and cooperation. Therefore, it can be concluded that expressive speech acts in Moana 2 have a significant role in character development, clarifying the emotional context of utterances, and effectively supporting the delivery of moral and cultural values within the narrative.